Conduction recovery with Wenckebach periodicity at the mitral isthmus. Issue 7 (12th March 2021) - Nakashima, Takashi; Pambrun, Thomas; Pintican, Gabriela; Takagi, Takamitsu; Jaïs, Pierre; Derval, Nicolas
Abstract: A Wenckebach periodicity at the mitral isthmus (MI) lesion has rarely been reported. We described a case presenting conduction recovery with Wenckebach periodicity at the posterior MI lesion after achieving the MI block. These findings demonstrate a pseudo MI block with Wenckebach periodicity owing to the pacing rate.